Alzheimer’s Disease: The Knowledge of Nurses Regarding the Clinical Aspects of the Disease - Silva, Robson Pereira da; Costa, Ivelise Fhrideriad Alves Furtado da (ID on line. Revista de psicologia, 2018)
Abstract: Objective: To quantify and analyze the scientific production on the knowledge of nurses regarding the etiological, clinical aspects of Alzheimer's disease (AD) and its inherent complications. Methods: this is an integrative review of publications published between 2016 and 2017. The articles analyzed were found by consulting the databases: Scientific Electronic Library Online and Virtual Health Library. We collected 428 articles with the descriptors DA, Nursing, and Diagnosis, 15 of which were selected. Results: predominance of studies addressing the diagnosis but without making reference to clinical aspects of the disease was observed, reinforcing the initial concerns of this survey. Research about this subject does not emphasize all clinical aspects, and the analysis of the knowledge for interventions by nurses is unfeasible. Conclusion: It is essential stay up-to-date to be able to adopt a professional conduct on the subject, directing the care so as to reduce the impacts of the disease.